Cyber-physical-social-thinking modeling and computing for geological information service system - Yueqin Zhu; Yongjie Tan; Ruixin Li; Xiong Luo (International Journal of Distributed Sensor Networks)
The serious geological hazards occurred frequently in the last few years. They have inflicted heavy casualties and property losses. Hence, it is necessary to design a geological information service system to analyze and evaluate geological hazards. With the development of computer and Internet service model, it is now possible to obtain rich data and process the data with some advanced computing techniques under network environment. Then, some technologies, including cyber-physical system, Internet of Things, and cloud computing, have been used in geological information management. Furthermore, the concept of cyber-physical-social-thinking as a broader vision of the Internet of Things was presented through the fusion of those advanced computing technologies. Motivated by it, in this article, a novel modeling and computing method for geological information service system is developed in consideration of the complex data processing requirement of geological service under dynamic environment. Specifically, some key techniques of modeling the information service system and computing geological data via cyber-physical system and Internet of Things are analyzed. Moreover, to show the efficiency of proposed method, two application cases are provided during the cyber-physical-social-thinking modeling and computing for geological information service system.